Development and validation of a real-time PCR assay for specific and sensitive detection of canid herpesvirus 1 - Decaro, Nicola (J Virol Methods, 2010)
A TaqMan-based real-time PCR assay targeting the glycoprotein B-encoding gene was developed for diagnosis of canid herpesvirus 1 (CHV-1) infection. The established assay was highly specific, since no cross-reactions were observed with other canine DNA viruses, including canine parvovirus type 2, canine minute virus, or canine adenovirus types 1 and 2. The detection limit was 10(1) and 1.20 × 10(1) DNA copies per 10 μl(−1) of template for standard DNA and a CHV-1-positive kidney sample, respectively: about 1-log higher than a gel-based PCR assay targeting the thymidine kinase gene. The assay was also reproducible, as shown by satisfactory low intra-assay and inter-assay coefficients of variation. CHV-1 isolates of different geographical origins were recognised by the TaqMan assay. Tissues and clinical samples collected from three pups which died of CHV-1 neonatal infection were also tested, displaying a wide distribution of CHV-l DNA in their organs. Unlike other CHV-1-specific diagnostic methods, this quantitative assay permits simultaneous detection and quantitation of CHV-1 DNA in a wide range of canine tissues and body fluids, thus providing a useful tool for confirmation of a clinical diagnosis, for the study of viral pathogenesis and for evaluation of the efficacy of vaccines and antiviral drugs.